Analysis of Barriers to Village Consultation Boards in Following up Village Community Aspirations for Democracy - Soleh, Mukhammad (LEGAL BRIEF, 2024)
Law Number 6 of 2014 concerning Villages states that the Village Consultative Body has the following functions: "a. discussing and agreeing on the Draft Village Regulation with the Village Head; b. accommodating and channeling the aspirations of the village community, and c. supervising the performance of the Village Head". Examine and evaluate the barriers that prevent the Village Consultative Body from carrying out its duties in a way that accommodates and directs the aspirations of the village community. Asrikaton Village, District, Malang Regency, was the research site for the empirical legal research method. The Village Head, Village Secretary, Chairman and Secretary of the Village Consultative Body, and Hamlet's Head are the sources of information. The results of the study found that the factors inhibiting the implementation of the functions of the Village Consultative Body in following up on the aspirations of the village community. a). Lack of intellectual qualities of personnel members of the Village Consultative Body. b). Members of the Village Consultative Council, busy with their lives in other jobs, work occupied before becoming a member of the Village Consultative Body. c). Operational budget support and infrastructure facilities from the Asrikaton Village Government are inadequate and minimal